Transcutaneous spinal direct current stimulation increases corticospinal transmission and enhances voluntary motor output in humans. Issue 16 (18th August 2020) - Yamaguchi, Tomofumi; Beck, Mikkel M.; Therkildsen, Eva R.; Svane, Christian; Forman, Christian; Lorentzen, Jakob; Conway, Bernard A.; Lundbye‐Jensen, Jesper; Geertsen, Svend S.; Nielsen, Jens B.
Abstract: Optimization of motor performance is of importance in daily life, in relation to recovery following injury as well as for elite sports performance. The present study investigated whether transcutaneous spinal direct current stimulation (tsDCS) may enhance voluntary ballistic activation of ankle muscles and descending activation of spinal motor neurons in able‐bodied adults. Forty‐one adults (21 men; 24.0 ± 3.2 years) participated in the study. The effect of tsDCS on ballistic motor performance and plantar flexor muscle activation was assessed in a double‐blinded sham‐controlled cross‐over experiment. In separate experiments, the underlying changes in excitability of corticospinal and spinal pathways were probed by evaluating soleus (SOL) motor evoked potentials (MEPs) following single‐pulse transcranial magnetic stimulation (TMS) over the primary motor cortex, SOL H‐reflexes elicited by tibial nerve stimulation and TMS‐conditioning of SOL H‐reflexes. Measures were obtained before and after cathodal tsDCS over the thoracic spine (T11‐T12) for 10 min at 2.5 mA. We found that cathodal tsDCS transiently facilitated peak acceleration in the ballistic motor task compared to sham tsDCS. Following tsDCS, SOL MEPs were increased without changes in H‐reflex amplitudes. The short‐latency facilitation of the H‐reflex by subthreshold TMS, which is assumed to be mediated by the fast conducting monosynaptic corticomotoneuronal pathway, was also enhanced by tsDCS. We argue that tsDCS briefly facilitates voluntary motor output by increasing descending drive from corticospinal neurones to spinal plantar flexor motor neurons. tsDCS can thus transiently promote within‐session CNS function and voluntary motor output and holds potential as a technique in the rehabilitation of motor function following central nervous lesions. Abstract : We aimed to investigate the effects of transcutaneous spinal direct current stimulation (tsDCS) on descending activation of spinal motor neurons in healthy adults. Cathodal tsDCS facilitated peak torque and acceleration of a ballistic motor task and increased both the motor evoked potentials of the soleus, and the short‐latency facilitation of the soleus H‐reflex. Therefore, we argue that tsDCS may be a useful technique for facilitating descending drive and promoting motor function following central nervous lesions.